Comparative Study of Macro Program Machining and CAM 2.5D Machining for Press Die Manufacturing - Permana, Al Kautsar; Aji, Reza Melliyanno Putra; Arohman, Abdul Wahid; Sumasto, Fredy; Agustin, Desy (JMPM (Jurnal Material dan Proses Manufaktur), 2024)
The manufacturing industry extensively utilizes machining and casting processes for die fabrication. Due to the inherent dimensional inaccuracies and surface roughness of casting, machining is often required to achieve desired accuracy and finish. Traditional computerized numerical control machining relies on individual programming using macro programming or computer-aided manufacturing software for operations such as facing, which can be inefficient and prone to error. This study aims to evaluate and compare the efficiency and accuracy of macro programming and CAM 2.5D in CNC milling specifically for press die manufacturing. Macro programming is used for automating complex and repetitive machining by incorporating variables, expressions, and logic directly to machine whereas CAM 2.5D refers to programming using software in G-code format with capability to work not only two-dimensional planes but also limited vertical movement. Experimental results indicate that CAM 2.5D offers a time-saving advantage by about 2 hours while macro programming allows for greater accuracy in machining. Industries are encouraged to utilize both macro programming and CAM 2.5D to achieve a balance of speed, accuracy, and flexibility, optimizing their CNC machining processes for both large-scale and precision-focused operations.